2019
DOI: 10.1103/physreve.100.062123
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in feedback-driven systems: Thermodynamics and noise

Abstract: Oscillations in nonequilibrium noisy systems are important physical phenomena. These oscillations can happen in autonomous biochemical oscillators such as circadian clocks. They can also manifest as subharmonic oscillations in periodically driven systems such as time-crystals. Oscillations in autonomous systems and, to a lesser degree, subharmonic oscillations in periodically driven systems have been both thoroughly investigated, including their relation with thermodynamic cost and noise. We perform a systemat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Numerous studies have explored the design principle of signaling circuits with various biological functions. The relationships between network motifs [26] (such as paradoxical components [27][28][29], feed-forward loop [30], and feedback loop [31][32][33]) and biochemical oscillator [34][35][36], adaptation [37], robustness [38][39][40][41], and noise attenuation [42][43][44] have been revealed successively. Designing and developing a signaling circuit system with regulatory function is of guiding significance for the further understanding of how oscillation signals regulate biological processes [13,45].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have explored the design principle of signaling circuits with various biological functions. The relationships between network motifs [26] (such as paradoxical components [27][28][29], feed-forward loop [30], and feedback loop [31][32][33]) and biochemical oscillator [34][35][36], adaptation [37], robustness [38][39][40][41], and noise attenuation [42][43][44] have been revealed successively. Designing and developing a signaling circuit system with regulatory function is of guiding significance for the further understanding of how oscillation signals regulate biological processes [13,45].…”
Section: Introductionmentioning
confidence: 99%
“…The energy harvester and the related model considered in our paper represent an instance of non-Markovian systems, where feedback mechanisms and memory effects are at play. These kinds of models have been the object of an intense study in recent years, from the point of view of stochastic thermodynamics [23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The modeling of containment measures in compartmentalized epidemic models [6] is thus under the focus of intense research [7,8]. It has been very recently rigorously demonstrated that compartimentalized epidemic models display oscillations in presence of feedback between infection rate and infection states [9],and that in general a feedback between order and control parameters in large interacting systems subject to phase transitions triggers self-oscillations [10,11], where an Andronov-Hopf bifurcation takes over the usual phase transition. As infection and recovery rates are changed, epidemic models on networks display out-of-equilibrium phase transitions between a phase where a disease is prevented from spreading and a phase where a finite fraction of the population becomes infected [12].…”
Section: Introductionmentioning
confidence: 99%